1989
DOI: 10.1002/jor.1100070416
|View full text |Cite
|
Sign up to set email alerts
|

A study of the mechanical strength of long bone defects treated with various bone autograft substitutes: An experimental investigation in the rabbit

Abstract: This study was designed to determine which of several bone grafting materials would be the most efficacious substitute for autogenous bone graft in the treatment of segmental long bone defects. The experimental model was a 1-cm defect in the rabbit ulna. The control group had nothing implanted in the defect. The six grafts tested were: (a) autogenous iliac crest bone, (b) autogenous cortical bone (ulna), (c) hydroxylapatite, (d) hydroxylapatite-demineralized bone matrix (allograft) composite graft, (e) freeze-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
46
0

Year Published

1991
1991
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(47 citation statements)
references
References 25 publications
1
46
0
Order By: Relevance
“…They designed an experiment in which the ulnar defects of rats were grafted by HA, DBM, HA/DBM, autogenous bone graft and allogenic bone graft in five different groups. At the sixth week, they found that the plain HA group scored worse than the control group, whereas all other groups displayed better scores [12].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…They designed an experiment in which the ulnar defects of rats were grafted by HA, DBM, HA/DBM, autogenous bone graft and allogenic bone graft in five different groups. At the sixth week, they found that the plain HA group scored worse than the control group, whereas all other groups displayed better scores [12].…”
Section: Discussionmentioning
confidence: 99%
“…Such problems led investigators in search of allografts, which have comparable results to the autografting procedures. As a result, some investigators used mixtures of synthetic scaffolding biomaterials and osteoinductive organic agents to achieve better results [1,12,14,19,20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature is contradictory on this point [5,10,13,14,18], as some authors emphasise the osteoinductive properties of this type of graft [28], while others underline the poor results [7,12] in both experimental and clinical studies. This is in agreement with the findings of our study.…”
Section: Discussionmentioning
confidence: 99%
“…It has already been shown that autologous bone grafts could provide healing of such a defect in a similar model. [25][26][27] We decided not to study a group with BMC alone because this cannot be used in clinical cases for such large defects of a long bone. The cell suspension needs a rigid scaffold or a gel to be maintained in the defect to avoid dispersion of the cells and formation of ectopic bone.…”
Section: Discussionmentioning
confidence: 99%